Adsorption of Mercury Using Different Types of Activated Bentonite: A Study of Sorption, Kinetics, and Isotherm Models - Naswir, Muhammad; Jalius, Jalius; Natalia, Desfaur; Arita, Susila; Wibowo, Yudha Gusti (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2020)
Mercury is a hazardous element because of its toxicity and harmful effects on human health. Various traditional and low-cost methods have been developed to remove mercury from wastewater. This study used local raw material as an alternative adsorbent to treat mercury-contaminated wastewater. Activated bentonite was prepared using different chemical activators (H3PO4, HCl, and ZnCl2) in various concentrations. Then, it was dried at 200C for an hour. The materials were characterized by SEM-EDS. Its percent removal and isotherm models were analyzed. In this study, the most effective activator was H3PO4 and the experimental data matched the Freundlich model.